THE STUDENTS’ FREE WRITING TOWARD ICT AS MEDIA IN ENGLISH LEARNING ON MIDWIFERY STUDENTS OF STIKES PEMBINA - Arief Pamuji (Universitas Tridinanti Palembang, 2020)
The objective of this research was to find out the description of The students’ free writing toward ICT as media in English learning on midwifery students of STIKES Pembina. The sample of this research was taken by using totaling sampling technique with 36 midwifery students from STIKES Pembina, that consist of 13 students from 2nd semester students and 23 students from 4th semester. The data was obtained based on every meeting during online learning, that was from the third meeting to the seventh meeting that consists of 5 days for obtaining the data. Then from the data analysis, it’s obtained that there was the good improvement response by writing English related to the material since the frist day to the fifith day that was 63% of students response to the 95% students response in the last day. During the implementation of online learning by using ICT (whatssapp group and edlink) the obstacle raised on students. Many factor that made the students can’t join the class and response. One of the factor was the access on internet in their hometown. Even had the obstacle the use of ICT can be good choice in conducting the teaching and learning EFL proces of midwifery students of STIKES Pembina PalembangKeywords: free writing and ICT.